(untitled) (Damascus University Journal of agriculture sciences, 2024)
the study was carried out at Urah Research Station/ Sewida Agricultural Scientific Research Center/ General Commission for Scientific Agricultural Research/ Syria in 2021 with the aim of studying the effect of seed priming treatment using salicylic acid (SA) on cucumber under drought stress conditions, where the seeds of cucumber plant were soaked (native cultivar) in four concentrations of SA (0, 1, 50, 150 mg/L) for 24 hours, and then cultivated under three different irrigation levels (60, 80, 100% from field capacity). The results showed that all morphological (stem length, number of leaves, dry and fresh weights), physiological (N, P, K concentration), and productive indicators (number and weight of fruits, yield) decreased with low level of applied irrigation, while soaking seeds with salicylic acid with the two concentrations (50, 150 mg/l) achieved a significant improvement in all the mentioned indicators compared to the control treatment, regardless of the field capacity, and the concentration of 50 mg/L was significantly superior compared to the control treatment in response to tested drought conditions, followed by 150 mg/ L concentration, and similarly the 50 mg/L was superior in most studied indicators in response to 100% irrigation level, and 50 mg/L concentration has achieved significantly differences compared to the control treatment for yield indicator registering 6608, 5687, 4856 kg/h in irrigation levels 100%, 80%, and 60% respectively. It can be said that seed priming treatments using Salicylic acid has achieved generally notable improvement in studied indicators in response to drought stress on field level, the research concluded that 50 mg/L treatment generally showed the best effect on most studied indicators under drought conditions.